Isolation and identification of novel antioxidant and antimicrobial oligopeptides from enzymatically hydrolyzed anchovy fish meal. (November 2018) - Wang, Limei; Sun, Jiang; Ding, Shuhui; Qi, Bin
Graphical abstract: Highlights: Four novel oligopeptide fractions were isolated from anchovy fish meal hydrolysate. Anti-oxidant activities of the isolates were observed. The isolates have suppression effects on Escherichia coli and Staphylococcus aureus . The isolates have no suppression effects on Aspergillus flavus and Candida albicans. Abstract: Natural Antioxidants and antimicrobials are preferred to prolong food shelf life, therefore we isolated and identified novel natural antioxidant and antimicrobial oligopeptides from anchovy fish meal hydrolysate. Firstly, the oligopeptide mixture was prepared by two-step hydrolysis using alkaline and neutral proteases step by step for enriching oligopeptides. Then, four novel oligopeptide fractions were purified using reversed phase-high performance liquid chromatography, and their sequences were determined using high performance liquid chromatography-time of flight-mass spectrometry. Meanwhile, antioxidant and antimicrobial activities of the fractions were evaluated. Thr-Pro-Ser-Ala-Gly-Lys exhibited the highest hydroxyl scavenging activity, lipid peroxidation inhibition, ferrous ion chelating activity as well as Escherichia coli growth inhibition. Thr-Pro-Ser-Asn-Leu-Gly-Gly-Lys showed the highest superoxide scavenging activity, lipid peroxidation inhibition, and Staphylococcus aureus growth inhibition. Leu-Glu and Leu-Glu-Glu displayed similarly high inhibition activity on 2, 2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid. Almost no suppression effects on Aspergillus flavus and Candida albicans growth were observed for all isolated fractions. These results indicate that the oligopeptide mixture derived from anchovy fish meal could serve as a suitable source of antioxidant and antimicrobial oligopeptides.